A Precarious Study of network propagation delay in Blockchain Technology - Pathan, Summiya A; Sharma, Dr. Yogesh Kumar (The journal of contemporary issues in business and government, 2021)
This paper analyses the Bitcoinblockchain selfish-mine strategy. A colluding group of miners could use this tactic to earn more than their fair share of mining profits and thereby forcefully join other honest men in decreasing the variance of their revenues and making their revenues more stable for months. It is a very dangerous dynamic that could enable the disbelieving mining body, accumulating news adherents' forces and manipulating the entire network, to enter the majority. Given that information spread between two miners in the network is not negligible and is accompanied by a normally distributed midway distribution proportional to the physical gap between the two miners, and by a permanent variance, regardless of other people's delays, we show that the success or failure of the attack on the selfish mines can not be assured due to uncertainty.